How to meet and talk to anyone, anywhere, anytime : simple strategies for great conversations - Brown, Marvin (Contact Strategies, 2013)
"Whether at a party, a wedding, a trade show, on vacation, or anywhere else, speaking to strangers is one of the biggest social fears people face. The reason? They don't know how! Marvin Brown has developed amazingly simple strategies and techniques that enable people to comfortably start and maintain conversations with confidence and ease."--P. [4] of cover.